Penyuluhan Irigasi Tetes Pada Masyarakat Di Dusun Dasan Tereng Desa Gumantar Kabupaten Lombok Utara - Negara, I Dewa Gede Jaya; Karyawan, I Dewa Made Alit; Rohani; Suparjo; Supriyadi, Anid; Budianto, M Bagus; Setiawan, Ery; Suroso, Agus; Sulistiyono, Heri; Eniarti, Miko; Pradjoko, Eko; Saadi, Yusron (Universitas Mataram, 2025)
The Gumantar Village community is a community located in the hills with terraced and sloping village conditions. Most of the community has yards and gardens, although not very large with terraced land conditions. The water source of the Gumantar Village Community comes from the upstream hillsides, with the number of hamlets as many as 16 hamlets with a population of around 2000 people and most of them are field farmers. Considering the potential of the surrounding land which is very large and in the form of terraces, it is necessary to provide counseling to the community on how to utilize limited water sources for farming activities with a drip irrigation system. To help the community, counseling is needed so that the community quickly understands the drip irrigation system. This community service aims to provide efficient irrigation counseling, namely drip irrigation, to encourage farming to be carried out around the yard. The community service consists of location survey activities, counseling, discussion and question and answer sessions, and evaluation. This community service has succeeded in providing counseling to 35 people consisting of housewives and fathers, as well as young people from the Dasan Tereng Hamlet mosque. Participants have gained knowledge about drip irrigation and obtained examples of the use of drip irrigation in yards and dry land, so that people are able to utilize limited water in the dry season for agricultural purposes in their yards